Plasma assisted carburization of CoPt/TiO2 catalysts with improved Fischer-Tropsch synthesis performance. (15th October 2019) - Xiao, Guiqin; Yan, Junkun; Du, Juan; Han, Yaoyao; Sun, Fenglou; Zhang, Yuhua; Li, Jinlin; Hong, Jingping
Graphical abstract: Highlights: "Reduction – carburization" processes in traditional hcp phase Co 0 preparation was substituted. Effective carburization could occur during direct CO plasma treatment on calcined precursor. The carburized catalyst presented higher specific site activity and better reaction stability. Abstract: Substitution of the time and energy consuming "reduction – carburization" processes in traditional hcp phase metallic cobalt preparation was achieved by fast and simple plasma technique. The CoPt/TiO2 -cal catalyst precursor used for plasma treatment was prepared via incipient wetness impregnation and calcined at 330 °C in air. Effect of plasma treating atmospheres including pure CO, first H2 then CO, first H2 then CO following H2 were studied. Characterization and catalytic results showed that effective carburization occurred during direct CO plasma treatment on calcined precursor. The formed cobalt carbide can be easily reduced at a low temperature (<200 °C) and selectively form hcp phase cobalt, which presented higher specific site activity (TOF) and better reaction stability, meanwhile, a lowest CH4 selectivity (6.8%) and highest C5+ selectivity (87.5%), in comparison with the other three catalysts forming mainly fcc phase Co 0 after H2 reduction.